Setting up of in-vacuum PIXE system for direct elemental analysis of thick solid environmental samples. (April 2016) - Rihawy, M.S.; Ismail, I.M.; Halloum, D.
Abstract: Experimental set-up, development, characterization, and calibration of an in-vacuum PIXE system at the tandem accelerator facility of the Atomic Energy Commission of Syria (AECS) is described. The PIXE system calibration involved experimental characterization of the X-ray detector parameters and careful determination of the H-values that control dependence of the detector solid angle with the X-ray energies and correct imperfect values of the detector efficiency. Setting up of an electron flood gun to compensate charge built up and utilization of a beam profile monitor to perform indirect measurement of the beam charge, provide a direct PIXE measurement of thick insulating samples in-vacuum. The PIXE system has been subsequently examined to verify its ability to perform direct PIXE measurements on geological materials. A combination of minimum sample preparation procedures and specific experimental conditions applied enables simple and accurate elemental analysis. Elemental concentrations of several elements heavier than sodium in different reference geological samples, at about 5–10% absolute accuracy for most elements, have been determined. Comprehensive discussion of the obtained elemental concentration values, for most elements of visible X-ray peaks in the PIXE spectra, has been considered. Highlights: Characterization and calibration of PIXE system of the tandem accelerator of AECS is discussed. The PIXE system has been established to perform direct PIXE measurements on geological materials. Elemental concentrations of geological samples was determined, at about 5–10% absolute accuracy.